Interstitial lung disease (ILD) in adult patients with autoimmune connective tissue disease (CTD) at Groote Schuur Hospital - Palalane, Elisa Assis (Department of Medicine, 2021)
Introduction. Interstitial lung disease (ILD) is prevalent in patients with autoimmune rheumatic diseases (ARD), leads to significant morbidity and mortality and is poorly characterized in South Africa (SA). We undertook this study to describe the clinical, serological and radiological features of ILD associated with ARD in a tertiary referral hospital. Methods. A cross-sectional study of patients with ILD attending the rheumatology and respiratory outpatient clinics of Groote Schuur Hospital between October 2018 and September 2019. Clinical, serological and radiological features were documented. We compared features of 3 groups of patients: rheumatoid arthritis (RA), systemic sclerosis (SSc) and other autoimmune connective tissue diseases (OCTD) which included idiopathic inflammatory myopathies, mixed connective tissue disease, systemic lupus erythematosus, primary Sjogren's syndrome and overlap syndromes. Factors associated with usual interstitial pneumonia (UIP) subtype were assessed. Results. Of 124 patients, 37 (29.8%) had RA, 32 (25,8%) SSc and 55 (44.4%) OCTD. Most patients were female (86.3%), of mixed racial ancestry (75.0%), and the median (IQR) age was 55 (46-66). Over one-third were smokers, emphysema was diagnosed in 22.6%, and one-third had previous pulmonary tuberculosis (PTB) infection. Smoking, emphysema, and previous PTB were higher in RA group but the difference was not statistically significant. All SSc patients and more than two-thirds of RA and OCTD patients had gastroesophageal reflux disease (GORD). Nonspecific interstitial pneumonia (NSIP) was the commonest pattern of ILD (63.7%), followed by usual interstitial pneumonia (UIP) (26.6%) and other patterns (9.7%). RA patients had similar frequencies of NSIP and UIP. Patients with RA were significantly older (median (IQR)) at ILD onset (62 (55-68) years), compared to SSc (49 (38-56)) and OCTD (42 (33-56)) (p < 0.001). Pulmonary function tests (PFTs) were significantly worse in SSc and OCTD groups. Regarding MTX exposure, 37.1% patients has MTX prescribed before ILD diagnosis, 33.9% continued, started or restarted after ILD diagnosis. No case of acute pneumonitis was documented. Pulmonary function tests and high-resolution computer tomography severity correlated poorly, with PFTs underestimating the severity. In the analysis comparing patients with and without UIP, RA diagnosis (OR 3.8, 95% CI 1.5-9.5), older age (0R 1.1, 95% CI 1.0-1.1), COPD (OR 3.2, 95% CI 1.4-8.0), longer ARD-ILD interval, and higher FVC (OR 1.0, 95% CI 1.0-1.1) were significantly associated with UIP. Conclusions: ILD was most commonly diagnosed in RA and SSc patients, with NSIP seen most frequently overall. Smoking, GORD, and PTB were frequent comorbidities. Amongst RA patients, we observed older age of onset and, interestingly, similar frequencies of NSIP and UIP patterns. The use of MTX was not associated with the development of acute pneumonitis in patients with ILD.